2017
DOI: 10.1016/j.jacr.2017.08.041
|View full text |Cite
|
Sign up to set email alerts
|

ACR Appropriateness Criteria ® Sinonasal Disease

Abstract: Imaging of sinonasal pathology may occur for assessment of rhinosinusitis or mass lesions. Rhinosinusitis is prevalent in up to 16% of the US population with annual economic burdens estimated at 22 billion dollars. Rhinosinusitis is characterized as acute or chronic based on symptom duration; if four or more episodes occur annually, the term recurrent acute rhinosinusitis (RARS) is used. In acute uncomplicated rhinosinusitis when inflammatory change remains in the paranasal sinuses and nasal cavity, imaging ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 51 publications
1
40
0
1
Order By: Relevance
“…It is possible that the degree of mucosal thickening on sinus CT unduly influenced the decision to treat with antibiotics, which should be based on history and examination. 6,7 Mucosal thickening on CT does not differentiate between bacterial and viral pathogens, and 3 of 5 patients receiving antibiotics in this study had nasal washes positive for viral pathogens. Next, only patients undergoing imaging work-up were considered symptomatic post-HCT.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…It is possible that the degree of mucosal thickening on sinus CT unduly influenced the decision to treat with antibiotics, which should be based on history and examination. 6,7 Mucosal thickening on CT does not differentiate between bacterial and viral pathogens, and 3 of 5 patients receiving antibiotics in this study had nasal washes positive for viral pathogens. Next, only patients undergoing imaging work-up were considered symptomatic post-HCT.…”
Section: Discussionmentioning
confidence: 67%
“…The American Academy of Pediatrics and American College of Radiology guidelines dictate that diagnosis and treatment of acute sinusitis should be clinical, with imaging reserved for suspicion of orbital or CNS complications. 6,7 IFRS typically presents with a combination of fever, facial pain, nasal congestion, headache, eye symptoms, and/or facial swelling, which should also prompt imaging, and likely endoscopy. [3][4][5]31 On pretransplantation physical examination, none of the 100 patients in our series had findings suggestive of orbital, CNS, or fungal involvement warranting imaging evaluation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The American College of Radiology publishes regularly updated appropriateness criteria on obtaining imaging tests for RARS, CRS, and invasive fungal sinusitis. 38 A multi-specialty, multi-national group developed appropriateness criteria for ESS as a management option for uncomplicated CRS. 39,40 Validation of the CRS appropriateness criteria demonstrated that these criteria predict outcomes for patients undergoing ESS for this disease in certain practice settings.…”
Section: Concha Bullosa 32mentioning
confidence: 99%
“…Headache accompanying clinical signs of meningitis should be managed by appropriate clinical guidelines. Please also reference the ACR Appropriateness Criteria Ò topic on "Head Trauma" [5], ACR Appropriateness Criteria Ò topic on "Cranial Neuropathy" [6], the ACR Appropriateness Criteria Ò topic on "Orbits Vision and Vision Loss" [7], the ACR Appropriateness Criteria Ò topic on "Sinonasal Disease" [8], and the ACR Appropriateness Criteria Ò topic on "Neuroendocrine Imaging" [9], in the appropriate clinical context. Headaches can be broadly classified into primary and secondary forms [1].…”
Section: Introduction/backgroundmentioning
confidence: 99%